2009
DOI: 10.1590/s0102-76382009000100017
|View full text |Cite
|
Sign up to set email alerts
|

Laser de baixa intensidade em deiscência aguda de safenectomia: proposta terapêutica

Abstract: Dehiscence is a feared complication after major surgeries. Patient who had undergone coronary artery bypass grafting developed saphenectomy's dehiscence on lower limb with edema and pain on the 15 th postoperative day. Conventional treatment had been initially performed without clinical improvement. On the 30 th postoperative day only Low Level Laser Therapy (LLLT) was applied punctually around surgical wounds edge. The results revealed granulated tissue, reduction of inflammatory process and analgesic effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 2 publications
0
12
0
4
Order By: Relevance
“…It is known today that this treatment modality helps in the resolution of inflammatory process with tissue repair of surgical wound by means of photobiomodulation of the tissues operated (13) . In previous studies, these benefits were also observed in surgical patients of several age groups who received the same treatment (4)(5)(6)(7)(8)(9) . The interaction of electromagnetic radiation takes place especially in a medium where unstable redox status is present (typical in situations of physiological stress), with stimulation of certain photoacceptor molecules existing both in the cell membrane and in the internal crest of mitochondrial membrane, and able to aid the damaged tissue to reach tissue homeostasis.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…It is known today that this treatment modality helps in the resolution of inflammatory process with tissue repair of surgical wound by means of photobiomodulation of the tissues operated (13) . In previous studies, these benefits were also observed in surgical patients of several age groups who received the same treatment (4)(5)(6)(7)(8)(9) . The interaction of electromagnetic radiation takes place especially in a medium where unstable redox status is present (typical in situations of physiological stress), with stimulation of certain photoacceptor molecules existing both in the cell membrane and in the internal crest of mitochondrial membrane, and able to aid the damaged tissue to reach tissue homeostasis.…”
mentioning
confidence: 58%
“…Several studies employing this method pointed to the efficacy of LLLT in tissue repair immediately after cardiovascular and orthopedic surgeries (3) . Laser therapy is able to prevent formation of postoperative dehiscence and it leads to faster functional recovery, thus reducing the duration of hospital stay (4)(5)(6)(7)(8)(9) . Its preventive use is noninvasive, painless and safe; additionally, it is an easy method to be used without the need of touching the lesion and can be performed at the hospital nursery.…”
mentioning
confidence: 99%
“…According Karu and Pinto (17,18) , this happens because the low energy intensity generates the process of biomodulation, which is the stimulation of the cell membrane and mitochondria, by the cellular energy increment, causing a synthesis of collagen by the fibroblast, recovering the energy function of the cell and the tissue repair.…”
Section: Discussionmentioning
confidence: 99%
“…É considerada uma terapia não invasiva, indolor, não térmica e assépti-ca, sem efeitos colaterais, com boa relação custo-benefí-cio, que, aliado à segurança do tratamento, justificam o crescente interesse dos pesquisadores quanto ao mecanismo de ação e seus efeitos terapêuticos 9 . Os lasers em baixa intensidade ou em fotobiomodulação são agentes terapêuticos sem potencial destrutivo, com eficiente ação anti-inflamatória e analgésica, fatores esses que ajudam no reparo dos tecidos biológicos traumatizados 10,11 . Também atuam na cicatrização pelo aumento do metabolismo, da proliferação e da maturação celular, aumento da quantidade de tecido de granulação e diminuição dos mediadores inflamatórios 12 .…”
Section: Introductionunclassified